Cytotoxic effects of methanol extract isolated from Erythrina fusca Lour on cancer cell-lines - Sismindari, Sismindari (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2003)
Background: Erythrina is a medicinal plant which is frequently used to treat cancer in Africa. People in Java, however, use Erythrina fusca (cangkring) to treat varicella and measles. Previous works demonstrated that the methanol extract of this plants leaves induced DNA topoisomerase II mediated DNA cleavage. This activity has been used widely as a target to find anticancer medicine. In order to be scientifically proofed the activity, therefore, it is necessary to analyze directly on the cancer cell-lines. Objectives: To identify the cytotoxicity effect of methanol extract of E. fusca leaves against cancer cell-lines.Methods: Cytotoxicity analysis of methanol extract isolated from E. fusca leaves was carried out against myeloma and HeLa S-3 cancer cell-lines, and to normal mononuclear cell. The level of cytotoxicity was determined by calculating the level of IC50 which was based on the percentage of the cell death following the 24 hours incubation with the extract.Results: It was demonstrated that this methanol extract was cytotoxic to myeloma and HeLa S-3 cell-lines with the IC50 of 0.005 mg/ml and IC50 of 0.08 mg/ml respectively. The percentage of the cell death on treated normal mononuclear cell with the extract, however, was very much low 110%). This was similar to that on the DMSO treated cells.Conclusion: The methanol extract isolated from E. fusca leaves was demonstrated had a selective cytotoxicity effect, as indicated by the level of the IC50 which was higher to myeloma compared to HeLa S3 cell-line, and had much less cytotoxic on normal mononuclear cells.Key words: Erythrina fusca, cytotoxicity, cancer cell-lines, mononuclear cell